2013
DOI: 10.1088/0004-637x/777/2/123
|View full text |Cite|
|
Sign up to set email alerts
|

On the Cluster Physics of Sunyaev-Zel'dovich and X-Ray Surveys. Iii. Measurement Biases and Cosmological Evolution of Gas and Stellar Mass Fractions

Abstract: Gas masses tightly correlate with the virial masses of galaxy clusters, allowing for a precise determination of cosmological parameters by means of large-scale X-ray surveys. However, the gas mass fractions ( f gas ) at the virial radius (R 200 ) derived from recent Suzaku observations of several groups are considerably larger than the cosmic mean, calling into question the accuracy of estimates of cosmological parameters. Here, we use a large suite of cosmological hydrodynamical simulations to study measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
128
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(153 citation statements)
references
References 139 publications
(209 reference statements)
23
128
2
Order By: Relevance
“…We note that our results for NCC systems are consistent with published results from SPH simulations (e.g. Battaglia et al 2013;Sembolini et al 2013;Planelles et al 2013) at scales of 0.1 Rvir, but are somewhat higher at larger radii.…”
Section: Gas Depletion Profilessupporting
confidence: 92%
“…We note that our results for NCC systems are consistent with published results from SPH simulations (e.g. Battaglia et al 2013;Sembolini et al 2013;Planelles et al 2013) at scales of 0.1 Rvir, but are somewhat higher at larger radii.…”
Section: Gas Depletion Profilessupporting
confidence: 92%
“…Therefore, we make a comparison with recent results from N-body hydrodynamical simulations of clusters that have aimed at measuring the evolution of the baryonic component. Figure 9 shows a comparison of the f gas from Battaglia et al (2013), who use hydrodynamical TreePM-SPH simulations including cooling, star-formation, and supernova and AGN feedback, with our results. Clearly both our single power law evolution and the broken mass-dependent evolution models are inconsistent with Battaglia et al (2013) predictions, which show a negligible change in f gas with redshift.…”
Section: F Gas Evolution Vs X-ray Data and Simulationsmentioning
confidence: 77%
“…Planelles et al 2013;Battaglia et al 2013;Le Brun et al 2014) have shown that energy injection around the cluster formation epoch may be able to expel some of the gas from the cores of halos (McCarthy et al 2011), leading to a depletion of baryons in the central regions. In particular, Planelles et al (2013) has found that the depletion factor Y b = f bar /(Ω b /Ω m ), where f bar denotes the cluster baryon fraction, reaches the value Y b = 0.85 at r 500 .…”
Section: Introductionmentioning
confidence: 99%